2015
DOI: 10.1007/s10534-015-9869-1
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis, characterization and theoretical calculations of (1,2-diaminocyclohexane)(1,3-diaminopropane)gold(III) chloride complexes: in vitro cytotoxic evaluations against human cancer cell lines

Abstract: The gold(III) complexes of the type (1,2-diaminocyclohexane)(1,3-diaminopropane)gold(III) chloride, [(DACH)Au(pn)]Cl3, [where DACH = cis-, trans-1,2- and S,S-1,2-diaminocyclohexane and pn = 1,3-diaminopropane] have been synthesized and characterized using various spectroscopic and analytical techniques including elemental analysis, UV-Vis and FTIR spectroscopy; solution as well as solid-state NMR measurements. The solid-state (13)C NMR shows that 1,2-diaminocyclohexane (1,2-DACH) and 1,3-diaminopropane (pn) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…Both CV and SWV demonstrated that in the presence of lysozyme all compounds 1–3 showed a substantial decrease in the peak current as well as a clear peak potential shift (Supplementary Figures S5, S6 and S7). The significant change of their redox state due to their interaction with lysozyme suggests a significative chemical interaction of such gold compounds and proteins [36]. This chemical aspect deserves high attention because it could be involved in the mechanism of action of these innovative molecules as anticancer drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Both CV and SWV demonstrated that in the presence of lysozyme all compounds 1–3 showed a substantial decrease in the peak current as well as a clear peak potential shift (Supplementary Figures S5, S6 and S7). The significant change of their redox state due to their interaction with lysozyme suggests a significative chemical interaction of such gold compounds and proteins [36]. This chemical aspect deserves high attention because it could be involved in the mechanism of action of these innovative molecules as anticancer drugs.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, assorted sets of a potential anti-tumor gold(III) compounds were synthesized and characterized, which exhibited significant anti-proliferative effects in vitro under similar physiological conditions. They include the gold(III) complexes of bipyridines [ 11 , 12 , 13 , 19 , 20 , 21 , 22 , 23 ], diamines [ 16 , 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], quinolones [ 16 ], dithiocarbamates [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], and porphyrinates [ 38 , 39 ], as well as dinuclear gold(III) complexes [ 13 , 22 , 23 ] and a variety of organogold(III) compounds [ 37 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel research, a team led by Altaf designed and synthesized other metallodrugs with anticancer activity, including gold (I) [21,22] and gold (III) complexes [23]. Together, our two research groups produced new bipyridine gold (III) dithiocarbamate complexes with nitrogen and sulfur donor ligands [24].…”
Section: Introductionmentioning
confidence: 99%